1977
DOI: 10.1037/0021-843x.86.6.589
|View full text |Cite
|
Sign up to set email alerts
|

Associative interference and premorbid adjustment in schizophrenia.

Abstract: The effects of associative interference on the verbal learning performance of male process and reactive schizophrenics and normals were studied using a mixed list with high and moderate interlist interference and new learning conditions. Schizophrenics made more errors than normals in the interference conditions but not in the new learning. Reactive schizophrenics made as many errors as the process group with high interference but significantly fewer under moderate interference. Process schizophrenics gave sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The process-reactive difference appeared unlikely to have resulted from confounding with the effects of age, I&, level of physiological arousal, institutionalization, or severity of current symptoms. The results of the present investigations also indicated that the greater effect of response interference on reactives found by Hirsch (1971) with males in a paired-associate verbal learning task with experimentally induced interference can be applied to interference conditions that result from the use of high and low commonality stimulus words in a word association task. …”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The process-reactive difference appeared unlikely to have resulted from confounding with the effects of age, I&, level of physiological arousal, institutionalization, or severity of current symptoms. The results of the present investigations also indicated that the greater effect of response interference on reactives found by Hirsch (1971) with males in a paired-associate verbal learning task with experimentally induced interference can be applied to interference conditions that result from the use of high and low commonality stimulus words in a word association task. …”
Section: Resultssupporting
confidence: 53%
“…Reactive schizophrenics are viewed as more normal in cognitive development, but under stress or when acutely disturbed, they are hypothesized to show a cognitative deficit associated with disorganization due t o response interference. Hirsch (1971), who used male Ss in a paired-associate verbal learning task, found that reactive schizophrenics showed the same pattern of increasing errors with increasing associative interference as did normals. The reactives made significantly more errors than normals did under high interference conditions, but not with moderate interference.…”
mentioning
confidence: 99%
“…This is precisely the response pattern that would be predicted if the associations of the hallucinators flowed into a parasitic memory pattern. Also, there is abundant evidence indicating disordered associations (Kelter, Cohen, Engel, List & Strohner 1977;, associative interference (Hirsch & DeWolfe 1977), and disturbed mnemonic organization (Koh, Kayton & Berry 1973;Maher, Manschreck & Rucklos 1980) in schizophrenics, although the memory systems studied here were short-term. An appeal of the parasitic memory model is that if a VH or voice corresponds to a single parasitic memory representation that is triggered by widely dissimilar and distant associations, then the result would be expected to be highly repetitive in content.…”
Section: Disturbances Of Associative Memorymentioning
confidence: 64%